Helicobacter pylori antimicrobial resistance rates in the central region of Portugal. (12th July 2014) - Almeida, N.; Romãozinho, J. M.; Donato, M. M.; Luxo, C.; Cardoso, O.; Cipriano, M. A.; Marinho, C.; Fernandes, A.; Calhau, C.; Sofia, C.; Megraud, F.
Abstract Helicobacter pylori resistance to antimicrobial agents is steadily increasing. It is extremely important to be aware of the local prevalence of antibiotic resistance so as to adjust treatment strategies. During this single‐centre, prospective study, we aimed to determine primary and secondary resistance rates of H. pylori to antibiotics as well as host and bacterial factors associated with this problem. Overall, 180 patients (131 female; mean age 43.4 ± 13.5 years; primary resistance 103; secondary resistance 77) with positive 13C‐urea breath test were submitted to upper endoscopy with gastric biopsies. Helicobacter pylori was cultured and antimicrobial susceptibility was determined by Etest and molecular methods. Clinical and microbiological characteristics associated with resistance were evaluated by logistic regression analysis. Among the 180 isolates 50% were resistant to clarithromycin (primary 21.4%; secondary 88.3%), 34.4% to metronidazole (primary 29.1%; secondary 41.6%), 33.9% to levofloxacin (primary 26.2%; secondary 44.2%), 0.6% to tetracycline and 0.6% to amoxicillin. Being female was an independent predictor of resistance to clarithromycin and metronidazole. Previous, failed, eradication treatments were also associated with a decrease in susceptibility to clarithromycin. History of frequent infections, first‐degree relatives with gastric carcinoma and low education levels determined increased resistance to levofloxacin. Mutations in the 23S rRNA and gyrA genes were frequently found in isolates with resistance to clarithromycin and levofloxacin, respectively. This study revealed that resistance rates to clarithromycin, metronidazole and levofloxacin are very high and may compromise H. pylori eradication with first‐line and second‐line empiric triple treatments in Portugal.